2016
DOI: 10.22161/ijeab/1.4.46
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis of Annual and Seasonal Rainfall in Tawa command Area

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…There are various techniques employed to analyze the trends and variability of precipitation and temperature , which can be broadly classified into two categories: ‘variability analysis’ and ‘trend analysis’ [ [21] , [22] , [23] , 25 , 26 ]. For this study we employ the coefficient of variation (CV) [ 44 ], ‘ the Mann-Kendall test’ [ [45] , [46] , [47] ],and ‘ Sen's estimator’ [ [48] , [49] , [50] , [51] ].…”
Section: Research Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are various techniques employed to analyze the trends and variability of precipitation and temperature , which can be broadly classified into two categories: ‘variability analysis’ and ‘trend analysis’ [ [21] , [22] , [23] , 25 , 26 ]. For this study we employ the coefficient of variation (CV) [ 44 ], ‘ the Mann-Kendall test’ [ [45] , [46] , [47] ],and ‘ Sen's estimator’ [ [48] , [49] , [50] , [51] ].…”
Section: Research Methodologiesmentioning
confidence: 99%
“…These tests are designed to handle these complexities effectively. The computations for the aforementioned analyses were carried out using various packages available in the R-project [ [48] , [49] , [50] ] and XLSTAT, 2021. These software tools provide a range of statistical functions and algorithms necessary for conducting comprehensive trend and variability analyses.…”
Section: Research Methodologiesmentioning
confidence: 99%
“…Consequently, recent research on groundwater recharge zones in various countries such as China, Iran, Saudi Arabia, Taiwan, etc. has revealed that the groundwater resource is diminishing [3][4][5][6][7][8][9][10][11][12][13]. Geophysical data with geospatial data have been integrated by many researchers [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine the groundwater level trend non-parametric method i.e., Mann Kendall was applied in Ghat Parbha River Basin (India), they applied regression analysis and Mann Kendall method to determine the relationship between the drought and groundwater level (Pathak and Dodamani, 2019). The effect of linear rainfall patterns at the study area was also evaluated using the Mann Kendall approach (Nema et al, 2016). Innovative trend analysis also provides graphical and statistical representation (Şen, 2017) which provides a more easier, simple and quick approach about trend analysis.…”
Section: Introductionmentioning
confidence: 99%